G238(P) Ensuring Safe Discharges from the Children's Assessment Unit: Improvement on Completion of Discharge Summaries. (24th May 2017) - Chan, S; Lythgoe, H; Goldberg, K
Abstract : Aim: Discharge summary is the primary mode of communication between secondary and primary care. It is vital that this document is successfully completed and transmitted in a timely manner to ensure safe discharge and prevent unnecessary readmissions. All patients admitted to secondary care require a discharge summary including patients attending the Children's Assessment Unit (CAU). It has been recognised that discharge summaries are not always completed promptly in our unit. Our aim of this audit is to improve the delay of the completion of discharge summaries in CAU. Method: We audited patients who have been reviewed by a doctor and discharged from CAU during 19 th –25 th September 2016. The delay between discharge and completion of discharge summary was reviewed using our hospital's electronic system (Nexis). We then introduced interventions including: 1. Encouraging nursing staff to prompt doctors to complete discharge summary before the patient leaves CAU; 2. Encouraging nursing staff to complete discharge check list including the question about completion of discharge summary; 3.To educate doctors on the importance of discharge summary completion by presenting in a local teaching session and displaying posters. We then re-audited over 21 st –27 th November looking at the delay of discharge summary completion. Our standard was that 100% of discharge summaries should be completed on the day of discharge. We compared the pre-intervention and post-intervention results using a Chi-squared test. Result: There were 80 patients in the pre-intervention period and 74 in the post-intervention period. Overall the discharge summary completion rate improved from 85% pre-intervention to 88% post-intervention, and of the discharges that were completed the longest delay has reduced from 30 days to 21 days after intervention. During the pre-intervention period, 12 (15%) patients had their discharge summary completed on the same day of discharge compared with 34 (46%) the post-intervention period (p<0.001). Conclusion: We have successfully improved the efficiency in discharge summary completion in CAU using simple prompting and education strategies. To further this we will introduce direct individualised feedback to improve performance and positive encouragement for doctors who have completed discharge summaries promptly.